PENGARUH PENERAPAN LKS BERORIENTASI STRATEGI PEMBELAJARAN PENINGKATAN KEMAMPUAN BERPIKIR (SPPKB) TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X DI SMA N 8 PADANG - Riza Fitriani (PILLAR OF PHYSICS EDUCATION, 2014)
This research based  on less students learning outcome on physics at school. One of the solution for this problem is through LKS application that oriented by Strategi Pembelajaran Peningkatan Kemampuan Berpikir (SPPKB). The purpose of this research is to observe the influence of LKS application that oriented by Strategi Pembelajaran Peningkatan Kemampuan Berpikir (SPPKB) to students learning outcome on physics in grade X of SMAN 8 Padang. The type of this research is quansi experiment with Randomized Control Group Only Design. The population of this research is grade X students of SMAN 8 Padang by using purposive sampling technique to take sample, where is X6 class as the experiment class and X8class as the control class. The data of this research is the learning outcome of cognitive, affective and psychomotor. The research instrument are objective test to the learning outcome of cognitive aspect, observation sheet to the learning outcome of affective aspect, and scoring rubric to the learning outcome of psychomotor aspect. The conclusion that can be take from the result of this research is there the influence of LKS application that oriented by Strategi Pembelajaran Peningkatan Kemampuan Berpikir (SPPKB) in students learning outcome on physics in grade X of SMAN 8 Padang in significant level 0,05